2023
DOI: 10.1039/d3ta00086a
|View full text |Cite
|
Sign up to set email alerts
|

Universal assembly of ordered Ag nanowire micromesh conductors on arbitrary substrates by manipulating the contact angle

Abstract: To obtain remarkable electrical homogeneity and thermal stability Ag nanowires (Ag NWs) conductor by depositing nanowires uniformly to reduce the local hot spots is desirable in many optoelectronics applications. Here...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…To maintain high conductivity under diverse deformations, metallic materials can be ingeniously designed into various patterns, such as serpentine-honeycomb structure [138]. Additionally, a range of nanostructured electrodes with excellent mechanical flexibility and electrical properties, including Ag NWs, graphene, and carbon nanotubes, have been extensively developed in flexible PDs [139][140][141].…”
Section: Flexibility and Reliabilitymentioning
confidence: 99%
“…To maintain high conductivity under diverse deformations, metallic materials can be ingeniously designed into various patterns, such as serpentine-honeycomb structure [138]. Additionally, a range of nanostructured electrodes with excellent mechanical flexibility and electrical properties, including Ag NWs, graphene, and carbon nanotubes, have been extensively developed in flexible PDs [139][140][141].…”
Section: Flexibility and Reliabilitymentioning
confidence: 99%
“…They found that the transparency and conductivity of the networks could be separately regulated by varying the mesh width and film thickness. Some research groups demonstrated a universal self-assembly method of ordered Ag nanowires by using the coffee-ring effect [13][14][15] . The AgNWs micromesh exhibited excellent transmittance of 86.6% and conductivity of 6 Ω/sq [16] .…”
Section: Introductionmentioning
confidence: 99%
“…To adapt to the natural environment, animals such as chameleon and octopus have gradually developed a unique function of skin color change after nature evolution. The thermochromic devices have been exploited to visualize the temperature stimulus with a color change for application in sensors , and displays, which can be considered an effective solution to overcome the limitation of relying only on terminals with complicatedly physical connections and immensely enhance information interaction in the fields of military equipment, security systems, and human–machine interaction. In this work, inspired by the reversible color-change property of chameleon skin, a bioinspired stretchable and adhesive multimodal chromotropic e-skin system (MCES) consisting of adhesive polydimethylsiloxane (a-PDMS), conformal liquid metal (LM), thermochromic inks, and bare PDMS encapsulation layer was proposed (Figure ), which was capable of simultaneously detecting and distinguishing multi-stimuli of pressure, temperature, and strain through triboelectric, thermochromic, and capacitive effects with disparate perceptive signals.…”
Section: Introductionmentioning
confidence: 99%